Surface-modified film, method for producing surface-modified film, and surface-modified substrate

A surface-modified membrane method using methacrylate monomers and reactive compounds forms a dense polymer brush with functional groups, addressing the challenges of high molecular weight monomers and high-pressure requirements, achieving enhanced substrate properties.

JP7618171B2Active Publication Date: 2025-01-21DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021115592
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-13
Publication Date
2025-01-21
Estimated Expiration
2041-07-13

AI Technical Summary

Technical Problem

Existing methods face challenges in forming dense polymer brushes with high molecular weight monomers due to bulk effects, leading to insufficient polymerization and limited membrane properties, particularly with acidic groups, and require high-pressure conditions that are impractical.

Method used

A method involving surface-initiated radical polymerization of methacrylate monomers, followed by reaction with reactive compounds, forms a dense polymer brush with functional groups like amino, hydroxyl, or carboxyl groups, achieving a thickness of 100 nm to 10 μm without high-pressure equipment, using methacrylate monomers like hydroxyalkyl methacrylate and glycidyl methacrylate, and reactive compounds such as carboxylic acid anhydrides.

Benefits of technology

The method enables easy introduction of functional groups, forming a thick polymer brush with unprecedented properties like water repellency, oil repellency, high liquid retention, and antibacterial properties on various substrates, overcoming the limitations of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618171000005
    Figure 0007618171000005
  • Figure 0007618171000001
    Figure 0007618171000001
  • Figure 0007618171000002
    Figure 0007618171000002
Patent Text Reader

Abstract

To provide a surface modified film that includes a surface modified polymer which is a concentrated polymer brush, by which even a functional group which has not been easily introduced can be easily introduced, and that easily modifies surfaces of various substrates, thereby can impart new characteristics to the substrates, and has a sufficient film thickness.SOLUTION: The surface modified film is a filmy material that includes a surface modified polymer which is a reactant of a precursor polymer which extends from a polymerization initiating group of the surface of a substrate, to which the polymerization initiating group is bonded, and has a constitutional unit derived from a methacrylate-based monomer (i) such as hydroxyalkyl methacrylate, with a reactive compound (ii) such as a chemical compound having an amino group; and that is provided on the surface of the substrate and has a film thickness of 100 nm to 10 μm. A graft density of the surface modified polymer on the surface of the substrate is 0.1 to 1 / nm2.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface-modified film, a method for producing a surface-modified film, and a surface-modified substrate. [Background technology]

[0002] As a method for modifying a substrate, a method is known in which a polymer having a group at its end capable of adsorbing or reacting with the substrate is applied to the substrate to form a physically or chemically bonded polymer layer on the substrate surface. Also known is a method in which a polymerizable group provided on the substrate surface is used as a starting point to polymerize a monomer to form a grafted polymer layer from the substrate surface.

[0003] In recent years, so-called "concentrated polymer brushes" have been studied, which are densely grafted onto a substrate using the technology of living radical polymerization developed in the 1990s. In these concentrated polymer brushes, polymer chains are grafted onto the substrate at high density with intervals of 1 to 4 nm. Such concentrated polymer brushes can modify the surface of a substrate, imparting characteristics such as low friction, suppression of protein adsorption, size exclusion properties, hydrophilicity, water repellency, etc. (e.g., Patent Documents 1 and 2, Non-Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-133434 A [Patent Document 2] JP 2010-261001 A [Non-patent literature]

[0005] [Non-Patent Document 1] Adv. Polym. Sci., 2006, 197, 1-45 [Non-Patent Document 2] J.Am.Chem.Soc.,2005,127,15843-15847 [Non-Patent Document 3] Polym. Chem., 2012, 3, 148-153 Summary of the Invention [Problem to be solved by the invention]

[0006] When a monomer with a large molecular weight is polymerized in order to graft a polymer onto the substrate surface at a higher density, it is difficult to form a dense polymer due to the bulkiness of the monomer, and it is not easy to form a dense polymer brush. In addition, the polymerization reaction of the monomer with a large molecular weight does not proceed sufficiently, making it difficult to form a polymer layer with a thickness required to modify the surface of the substrate. Furthermore, when attempting to form a dense polymer brush by living radical polymerization methods such as atom transfer radical polymerization, there is a problem that the properties of the surface modification film to be formed are limited because it is difficult to polymerize monomers having acidic groups such as carboxy groups.

[0007] The present invention has been made in consideration of the problems of the prior art, and the object of the present invention is to provide a surface-modified film having a sufficient thickness, which includes a surface-modified polymer that is a dense polymer brush into which even functional groups that were not easily introduced can be easily introduced, and which can easily modify the surface of various substrates to impart new properties. The object of the present invention is to provide a method for producing the above-mentioned surface-modified film, and a surface-modified substrate having the above-mentioned surface-modified film. [Means for solving the problem]

[0008] That is, according to the present invention, there is provided a surface modified film as shown below. [1] A film-like substance having a thickness of 100 nm to 10 μm provided on the surface of a substrate, the film-like substance comprising a precursor polymer extending from a polymerization initiation group of a substrate having a polymerization initiation group bonded to its surface, the precursor polymer having a constitutional unit derived from a methacrylate monomer (i), and a reactive compound (ii), the precursor polymer being a reaction product of the polymerization initiation group and the reactive compound (ii), the methacrylate monomer (i) being at least one selected from the group consisting of hydroxyalkyl methacrylate, glycidyl methacrylate, epoxycyclohexylmethyl methacrylate, methacryloyloxyethyl isocyanate, and methacryloyloxyethyl isocyanate derivatives in which an isocyanate group is blocked, the reactive compound (ii) being at least one selected from the group consisting of compounds having an amino group, a hydroxyl group, or a carboxy group, a carboxylic acid anhydride, and an acid halide, the graft density of the surface-modifying polymer on the surface of the substrate being 0.1 to 1 strand / nm 2 A surface modified membrane. [2] The surface modified film according to [1], wherein the polymerization initiating group is a group represented by the following general formula (1):

[0009] TIFF0007618171000001.tif31170 (In the general formula (1), R1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group, R2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and Y represents O or NH.)

[0010] [3] The surface modified film according to [1] or [2], wherein the precursor polymer has a number average molecular weight of 200,000 to 5,000,000 and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.05 to 2.0. [4] The surface modified film according to any one of [1] to [3] above, which is a film-like object having a thickness of 400 nm to 10 μm. [5] The surface modified film according to any one of [1] to [4], wherein the reactive compound (ii) has a molecular weight of 500 to 20,000. [6] The surface modified film according to any one of [1] to [5], wherein the reactive compound (ii) is at least one of a compound having a polyalkylene glycol chain and a compound having a polydimethylsiloxane chain.

[0011] Furthermore, according to the present invention, there is provided a method for producing a surface modified film as described below. [7] A method for producing a surface-modified film according to any one of [1] to [6] above, comprising the steps of: (1) subjecting at least one methacrylate monomer (i) selected from the group consisting of hydroxyalkyl methacrylate, glycidyl methacrylate, epoxycyclohexylmethyl methacrylate, methacryloyloxyethyl isocyanate, and methacryloyloxyethyl isocyanate with a blocked isocyanate group to surface-initiated radical polymerization or surface-initiated living radical polymerization under a pressure condition of normal pressure to 1,000 MPa in the presence of a substrate having a polymerization initiator group bonded to its surface to form a precursor polymer layer containing a precursor polymer extended from the polymerization initiator group; and (2) reacting at least one reactive compound (ii) selected from the group consisting of a compound having an amino group, a hydroxyl group, or a carboxy group, a carboxylic acid anhydride, and an acid halide with the precursor polymer to form a surface-modified film containing a surface-modified polymer. [8] The method for producing a surface modified film according to [7], wherein in the step (1), the methacrylate (i) is subjected to surface-initiated living radical polymerization under a pressure condition of 10 to 500 MPa.

[0012] Further, according to the present invention, there is provided a surface-modified substrate as shown below. [9] A surface-modified substrate comprising a substrate and a surface-modified film according to any one of [1] to [6] provided on a surface of the substrate. Effect of the Invention

[0013] According to the present invention, it is possible to provide a surface-modified film having a sufficient thickness, which includes a surface-modified polymer that is a dense polymer brush into which even functional groups that have not been easily introduced can be easily introduced, and which can easily modify the surfaces of various substrates to impart new properties. In addition, according to the present invention, it is possible to provide a method for producing the above-mentioned surface-modified film, and a surface-modified substrate having the above-mentioned surface-modified film.

[0014] According to the present invention, even if a polymer is composed of a monomer that has been extremely difficult to form into a dense and sufficient film thickness, a dense polymer brush, which is a monomolecular chain layer, can be easily formed on the surface of a substrate, and a surface-modified substrate can be obtained whose surface is endowed with unprecedented properties. Specifically, it is expected that the substrate surface can be endowed with properties such as water repellency, oil repellency, high liquid retention in accordance with the liquid medium, high lubricity, extremely low friction, contamination resistance, antibacterial properties, and antiviral properties. [Brief description of the drawings]

[0015] [Figure 1] 1 shows surface infrared (IR) absorption spectra of the precursor polymer layer (1) and CPB-1 to CPB-3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Surface modified film and its manufacturing method> Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. The surface-modified film of the present invention is a film-like substance having a thickness of 100 nm to 10 μm, which is provided on the surface of a substrate and contains a surface-modified polymer which is a reaction product of a precursor polymer and a reactive compound (ii). The precursor polymer is a polymer having a constitutional unit derived from a methacrylate-based monomer (i) and extending from a polymerization initiation group of a substrate having a polymerization initiation group bonded to its surface. The methacrylate-based monomer (i) is at least one selected from the group consisting of hydroxyalkyl methacrylate, glycidyl methacrylate, epoxycyclohexylmethyl methacrylate, methacryloyloxyethyl isocyanate, and a methacryloyloxyethyl isocyanate derivative in which an isocyanate group is blocked. The reactive compound (ii) is at least one selected from the group consisting of a compound having an amino group, a hydroxyl group, or a carboxy group, a carboxylic anhydride, and an acid halide. The graft density of the surface-modified polymer on the surface of the substrate is 0.1 to 1 / nm 2 It is.

[0017] The method for producing the surface-modified film of the present invention is a method for producing the above-mentioned surface-modified film, and includes a step (1) of forming a precursor polymer layer, and a step (2) of reacting a reactive compound (ii) with the precursor polymer to form a surface-modified film containing a surface-modified polymer. Step (1) is a step of performing surface-initiated radical polymerization or surface-initiated living radical polymerization of the above-mentioned methacrylate monomer (i) under a pressure condition of normal pressure to 1,000 MPa in the presence of a substrate having a polymerization initiation group bonded to its surface, to form a precursor polymer layer containing a precursor polymer stretched from the polymerization initiation group. Step (2) is a step of reacting the above-mentioned reactive compound (ii) with the precursor polymer to form a surface-modified film containing a surface-modified polymer. The surface-modified film of the present invention and the method for producing the same will be described in detail below.

[0018] The graft density of the surface modification polymer on the surface of the substrate is 0.1 to 1 / nm 2The surface-modified film has a structure in which the polymer is densely formed on the surface of the substrate. For this reason, the surface-modified film substantially composed of such a surface-modified polymer is also called a dense polymer brush.

[0019] A typical concentrated polymer brush is usually formed by surface-initiated radical polymerization, preferably surface-initiated living radical polymerization. Among living radical polymerizations, atom transfer radical polymerization (ATRP), which is easy to introduce an initiator group, is generally used. In this ATRP method, an organic halide is used as an initiator group, and a complex of a metal ion such as a copper ion or a ruthenium ion with a polyamine as a ligand is used as a catalyst. This catalyst extracts a halogen atom from the initiator group as a radical, changes the valence of the metal ion, and stabilizes the structure of the metal halide salt. The residue of the organic halide generated by extracting the halogen atom becomes an organic radical. A monomer is added to this organic radical, and polymerization proceeds. However, since the generated organic radical is unstable, it extracts a halogen atom as a radical from the catalyst that has become a metal halide salt and bonds with it, becoming the original organic halide and stabilizing it. This prevents termination reactions such as coupling of the organic radical. The valence of the catalyst of the metal ion from which the halogen atom has been extracted returns to the original state. That is, the ATRP method is a polymerization method that utilizes an oxidation-reduction reaction, and a polymer grows by repeating the oxidation-reduction reaction, where the monomers are polymerized with organic halides as initiator groups. Since the radical concentration is low in this polymerization reaction, the monomers grow by adding one to several molecules at a time, and a polymer with a relatively uniform molecular weight is produced. By applying this ATRP method to surface-initiated living radical polymerization, it is possible to form a dense polymer brush.

[0020] However, when using a high molecular weight monomer, the bulkiness of the monomer makes it difficult to polymerize uniformly, making it difficult to form a thick polymer brush. In addition, since the ATRP method uses polyamines as ligands, if an acidic monomer is used, the metal complex is destroyed, the polymerization reaction does not proceed, and no polymer is produced. In addition, the type of ligand, polymerization conditions, and composition must be set according to the monomer and organic solvent, which is complicated. Furthermore, to form a thicker thick polymer brush, polymerization must be performed under pressure of about 400 MPa, but equipment that can withstand such high pressure is special and difficult to obtain.

[0021] In the method for producing the surface-modified film of the present invention, first, the above-mentioned methacrylate monomer (i) is polymerized to form a precursor polymer layer containing a precursor polymer that is a dense polymer brush (step (1)). Next, the above-mentioned reactive compound (ii) is reacted with reactive groups in the precursor polymer, such as hydroxyl groups, epoxy groups, and (blocked) isocyanate groups, to generate a surface-modified polymer that is a dense polymer brush having various properties derived from the reactive compound, thereby forming a surface-modified film (step (2)).

[0022] In the method for producing a surface-modified film of the present invention, it is not necessary to prepare a monomer having a specific function in advance, and it is not necessary to adjust the reaction conditions according to the type of monomer. That is, the surface-modified film can be produced by simply setting polymerization conditions suitable for the methacrylate monomer (i) and reacting the reactive compound (ii) exhibiting the desired characteristics. Furthermore, compared with the conventional production method in which a sufficient film thickness could not be obtained unless the film was under high pressure conditions, the production method of the present invention makes it possible to easily form a surface-modified film having a sufficient film thickness. In addition, by reacting the reactive compound (ii) with the precursor polymer constituting the precursor polymer layer, the film thickness of the precursor polymer layer can be further increased, and an even thicker surface-modified film can be produced.

[0023] In addition, according to the manufacturing method of the present invention, by reacting a high molecular weight reactive compound (ii) with a precursor polymer, a surface-modified polymer that is a high molecular weight dense polymer brush, which has been difficult to produce in the past, can be formed, and a surface-modified membrane can be obtained. Furthermore, even a surface-modified membrane containing a surface-modified polymer having a functional group such as an acidic group, which has been difficult to form by living radical polymerization, can be easily formed.

[0024] The precursor polymer is a polymer stretched from a polymerization initiator group bonded to the surface of the substrate, and has a constitutional unit derived from a methacrylate monomer (i). The methacrylate monomer (i) is at least one selected from the group consisting of hydroxyalkyl methacrylate, glycidyl methacrylate, epoxycyclohexylmethyl methacrylate, methacryloyloxyethyl isocyanate, and a methacryloyloxyethyl isocyanate derivative in which the isocyanate group is blocked.

[0025] Examples of the hydroxyalkyl methacrylate include hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, etc. Examples of the methacryloyloxyethyl isocyanate derivative in which the isocyanate group is blocked include 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl methacrylate, 2-[0-(1'-methylpropylideneamino)carboxyamino]ethyl methacrylate, etc.

[0026] The precursor polymer may have a structural unit (other structural unit) other than the structural unit derived from the methacrylate monomer (i). The other structural unit can be formed, for example, by using a methacrylate (other methacrylate) other than the methacrylate monomer (i). Examples of the other methacrylate include aliphatic alkyl, alicyclic alkyl, and aromatic methacrylates such as methyl, ethyl, propyl, butyl, isobutyl, t-butyl, hexyl, octyl, 2-ethylhexyl, decyl, isodecyl, dodecyl, stearyl, behenyl, cyclohexyl, t-butylcyclohexyl, trimethylcyclohexyl, tricyclodecyl, isobornyl, adamantyl, phenyl, and benzyl; methacrylates that are esters of alcohols having oxygen, nitrogen, fluorine, chlorine, silicon, and the like, such as tetrahydrofurfuryl, dimethylaminoethyl, diethylaminoethyl, t-butylaminoethyl, trifluoromethyl, perfluorooctyl, 3-chloro-2-hydroxypropyl, and trimethylsilyl; and the like. However, it is preferable to avoid the use of methacrylates having an excessively large molecular weight, methacrylates having an acidic group such as a carboxy group, and methacrylates capable of reacting with the methacrylate monomer (i).

[0027] The proportion of structural units derived from the methacrylate monomer (i) contained in the precursor polymer is preferably 30% by mass or more, more preferably 50% by mass or more, and particularly preferably 75% by mass or more.

[0028] The other structural units can be formed using monomers such as vinyl monomers and acrylates other than methacrylates. However, if the precursor polymer contains structural units derived from monomers such as vinyl monomers and acrylates, the surface-modified film formed may be too soft or too hard, the mechanical properties may be reduced, the polymerization rate may be reduced, and it may be difficult to control the increase in molecular weight. For this reason, it is preferable that the surface-modified film of the present invention is formed by a polymer substantially composed of a methacrylate monomer.

[0029] The reactive compound (ii) is at least one selected from the group consisting of a compound having an amino group, a hydroxyl group, or a carboxyl group, a carboxylic acid anhydride, and an acid halide. The acid halide is, for example, any one of an acid chloride, an acid bromide, and an acid iodide.

[0030] When a hydroxyalkyl methacrylate is used as the methacrylate monomer (i), an ester bond can be formed by reacting a compound having a carboxyl group, a carboxylic anhydride, or an acid halide with a hydroxyl group in a structural unit derived from the hydroxyalkyl methacrylate. Among them, reacting a carboxylic anhydride or an acid halide is preferable because it does not require an esterification catalyst such as a carbodiimide, and does not require dehydration condensation by high temperature heating, compared with the case of reacting a compound having a carboxyl group.

[0031] When glycidyl methacrylate or epoxycyclohexylmethyl methacrylate (methacrylate having an epoxy group) is used as the methacrylate monomer (i), it is preferable to react a compound having an amino group, a compound having a carboxy group, or a carboxylic anhydride. By reacting a compound having an amino group, the epoxy group is opened to form a hydroxyl group and an amino group. In addition, by reacting a compound having a carboxy group or a carboxylic anhydride, the epoxy group is opened to form a hydroxyl group and an ester bond. If an alkyl halide or the like is further reacted with the formed amino group, a quaternary ammonium base can be formed. In addition, an acidic substance can be reacted with the formed amino group to form a neutralized salt. A compound having an isocyanate group, an acid anhydride, and an acid halide can also be reacted with the formed hydroxyl group or amino group.

[0032] When methacryloyloxyethyl isocyanate or a methacryloyloxyethyl isocyanate derivative is used as the methacrylate monomer (i), it is preferable to react a compound having an amino group, a compound having a hydroxyl group, or a compound having a carboxyl group. By reacting a compound having an amino group, a urea bond can be formed. By reacting a compound having a hydroxyl group, a urethane bond can be formed. By decarbonating after reacting a compound having a carboxyl group, an amide bond can be formed.

[0033] Examples of the reactive compound (ii) include compounds having an amino group, such as alkyl and heterocyclic mono-, di- and polyamines, including stearylamine, dimethylaminoethylamine, dimethylaminopropylamine and aminomethylpyridine; compounds having a hydroxyl group, such as isostearyl alcohol and benzyl alcohol; compounds having a carboxy group, such as stearic acid, acrylic acid, methacrylic acid and benzoic acid; carboxylic acid anhydrides, such as phthalic anhydride, succinic anhydride and trimellitic anhydride; and acid halides, such as acrylic acid chloride and stearyl chloride.

[0034] For example, when a precursor polymer is formed using a methacrylate monomer (i) having an epoxy group or an isocyanate group, a reactive compound (ii) (e.g., dimethylaminopropylamine, etc.) having a primary amino group that reacts with an epoxy group or an isocyanate group and a tertiary amino group that does not react with an epoxy group or an isocyanate group can be reacted with the precursor polymer to form a surface-modified film having a tertiary amino group introduced therein. Since the tertiary amino group is basic, a basic surface-modified film can be formed. Furthermore, a quaternary ammonium base can be formed by reacting a quaternary chlorinating agent such as benzyl chloride with the tertiary amino group. The surface-modified film having a quaternary ammonium base introduced therein is expected to exhibit effects such as hydrophilicity and antibacterial properties. In addition, the tertiary amino group can be neutralized with an acidic compound to be ionized.

[0035] The molecular weight of the reactive compound (ii) is preferably 500 to 20,000, more preferably 1,000 to 5,000. According to the production method of the present invention, by using such a high molecular weight reactive compound (ii), it is possible to obtain a surface-modified film containing a surface-modified polymer that is a dense polymer brush in which high molecular weight polymers are densely arranged, which was difficult to produce by conventional methods.

[0036] Examples of the high molecular weight reactive compound (ii) include amino group-containing polymers such as polyethylene propylene oxide monomethyl ether monoamine, polyethyleneimine, polydimethylsiloxane diamine, etc.; terminal hydroxyl group polymers such as polyethylene glycol monomethyl ether, polypropylene glycol monobutyl ether, polytetramethylene glycol, polyepsilon caprolactone, etc. Furthermore, the reactive compound (ii) is preferably at least one of a compound having a polyalkylene glycol chain and a compound having a polydimethylsiloxane chain.

[0037] In addition, compounds having a carboxy group such as phthalic acid, cyclohexanedicarboxylic acid, cyclohexenedicarboxylic acid, trimellitic acid, pyromellitic acid, and tetrabutanoic acid: by using these acid anhydrides as the reactive compound (ii), it is possible to form a surface-modified film composed of a surface-modified polymer into which a carboxy group has been introduced.

[0038] It is most preferable to react all reactive groups (hydroxyl group, epoxy group, (blocked) isocyanate group) in the precursor polymer with the reactive compound (ii), but it is sufficient that the reactive groups in the precursor polymer react at a ratio that allows a specific performance derived from the reactive compound (ii) to be exhibited. When the reactive compound (ii) does not penetrate to the root of the precursor polymer (the deepest part of the precursor polymer layer) and reacts only halfway through the precursor polymer, a surface-modified film composed of a surface-modified polymer having a block structure can be formed. In addition, by reacting two or more types of reactive compounds (ii) with the precursor polymer, a surface-modified film composed of a surface-modified polymer having a so-called random structure in which two or more units derived from the reactive compound (ii) are introduced can be formed.

[0039] The surface-modified film is preferably a film having a thickness of 100 nm to 10 μm, more preferably 200 nm to 8 μm, and particularly preferably 400 nm to 5 μm. If the film thickness is less than 100 nm, the film may not perform as a surface-modified film, and the film thickness is thin, so that durability and the like tend to be insufficient. On the other hand, in order to obtain a film thickness of more than 10 μm, the molecular weight of the polymer needs to be very large, so that the polymerization time becomes excessively long and the molecular weight distribution of the obtained polymer may become too broad.

[0040] The graft density of the surface modification polymer on the surface of the substrate is 0.1 to 1 / nm 2 , preferably 0.15 to 0.7 lines / nm 2 The graft density is expressed as 2 ) is the number (strands) of surface-modifying polymers formed on the surface of the substrate. The surface-modifying polymers start from the polymerization initiator groups bonded to the surface of the substrate and stretch in a direction perpendicular to the substrate to form a surface-modifying film. By keeping the graft density of the surface-modifying polymer within the above range, unprecedented properties such as high elasticity, ultra-low friction, and size exclusion effect are exhibited. Note that when the graft density is 0.1 strands / nm 2 If the number is less than 1, the performance is not sufficient.2 It is difficult to achieve ultrahigh graft densities.

[0041] Graft density of surface-modifying polymer (σ: strands / nm 2 ) can be calculated according to the following formula (1). The thickness of the surface-modified film can be measured according to a conventionally known method using, for example, an ellipsometer, an electron microscope, an atomic force microscope, or the like. The density of the surface-modified polymer can be a value described in a conventionally known document, or a value measured according to a method described in JIS K 7112:1999, or the like. σ = dLNAMn (1) d: density of polymer (surface modified polymer) L: Thickness of the polymer layer (surface modification film) NA: Avogadro's number Mn: Number average molecular weight of the polymer (surface-modified polymer)

[0042] The graft density of the surface-modified polymer can be estimated to be the same as the graft density of the precursor polymer, which is its precursor. The number-average molecular weight (Mn) of the precursor polymer is preferably 200,000 to 5,000,000, more preferably 400,000 to 3,000,000. The molecular weight distribution (PDI=weight-average molecular weight (Mw) / number-average molecular weight (Mn)) of the precursor polymer is preferably 1.05 to 2.0, more preferably 1.1 to 1.8. In this specification, the number-average molecular weight (Mn) and the weight-average molecular weight (Mw) are both values ​​measured by gel permeation chromatography (GPC) in terms of polystyrene. By setting the number-average molecular weight and the molecular weight distribution of the precursor polymer within the above ranges, a surface-modified film with a higher graft density formed of the surface-modified polymer can be obtained. In addition, since the molecular weight distribution is relatively narrow, the growing ends of the surface-modifying polymer are relatively uniform, and the surface of the surface-modified film can be made flat to a certain extent.

[0043] If the number average molecular weight of the precursor polymer is less than 200,000, the thickness of the surface modified film tends to be insufficient, whereas if the number average molecular weight of the precursor polymer is more than 5,000,000, the polymerization takes a long time and the molecular weight distribution may become too broad.

[0044] It is practically difficult to obtain a precursor polymer with a PDI of less than 1.05, whereas if the precursor polymer has a PDI of more than 2.0, the molecular weight distribution is too broad, and the performance of the concentrated polymer brush may not be fully demonstrated.

[0045] The Mn and Mw of the precursor polymer can be measured by removing the precursor polymer from the substrate. Methods for removing the precursor polymer from the substrate include a method of treating with hydrofluoric acid or concentrated alkali, a method of hydrolysis, and the like. In addition, a precursor polymer can be formed by polymerizing a methacrylic acid monomer (i) in the presence of a compound having a polymerization initiator group (so-called a free initiator compound), and the Mn and Mw of the polymer stretched from the free initiator compound can be estimated as the Mn and Mw of the precursor polymer.

[0046] In the presence of a substrate having a polymerization initiating group bonded to its surface, a methacrylate monomer (i) is subjected to surface-initiated radical polymerization, preferably surface-initiated living radical polymerization, to form a precursor polymer layer containing a precursor polymer extended from the polymerization initiating group.

[0047] Examples of the polymerization initiator group include organic azo groups and organic peroxide groups. However, when these groups are used as the polymerization initiator group, the radicals generated have a short life span, and the polymerization is likely to stop midway. This can lead to insufficient film thickness and difficulty in forming a dense polymer brush. On the other hand, living radical polymerization initiator groups using organic halides, organic nitroxide compounds, organic thioester compounds, organic dithiocarbonate compounds, and organic tellurium compounds can also be used. However, it is complicated and difficult to form a polymerization initiator group using these compounds.

[0048] Therefore, it is preferable to use a polymerization initiating group formed using an easily available organic halogen compound as the polymerization initiating group. In particular, the polymerization initiating group bonded to the surface of the substrate is preferably a group represented by the following general formula (1).

[0049] TIFF0007618171000002.tif31170 (In the general formula (1), R1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group, R2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and Y represents O or NH.)

[0050] The polymerization initiator group represented by the general formula (1) can be bonded to the surface of various substrates according to a conventional method. Examples of the group represented by the general formula (1) include 2-chloropropanoyloxy group, 2-bromopropanoyloxy group, 3-iodopropanoyloxy group, 2-chloropropanoylamino group, 2-bromopropanoylamino group, 2-iodopropanoylamino group, 2-chloro-2-methylpropanoyloxy group, 2-bromo-2-methylpropanoyloxy group, 2-iodo-2-methylpropanoyloxy group, 2-chloro-2-methylpropanoylamino ...iodo-2-methylpropanoyloxy group, 2-chloro-2-methylpropanoylamino group, 2-iodo-2-methylpropanoyloxy group, 2-iodo-2-methylpropanoyloxy group, 2-iodo-2-methylpropanoyloxy group, 2-iodo-2-methylpropanoyloxy group, 2-iodo-2-methylpropano -Bromo-2-methylpropanoylamino group, 2-iodo-2-methyl-propanoylamino group, 2-chlorobutanoyloxy group, 2-bromobutanoyloxy group, 3-iodobutanoyloxy group, 2-chlorobutanolamino group, 2-bromobutanoylamino group, 2-iodobutanoylamino group, chlorophenylacetyloyloxy group, bromophenylacetyloyloxy group, iodophenylacetyloyloxy group, chlorophenylacetyloylamino group phenylacetyloylamino group, bromophenylacetyloylamino group, iodophenylacetyloylamino group, chloromethylphenylacetyloyloxy group, bromomethylphenylacetyloyloxy group, iodomethylphenylacetyloyloxy group, chloromethylphenylacetyloylamino group, bromomethylphenylacetyloylamino group, iodomethylphenylacetyloylamino group, chlorodiphenylacetyloyloxy group, bromodiphenylacetyloyloxy group Examples of the aryl group include an iododiphenylacetyloyloxy group, a chlorodiphenylacetyloylamino group, a bromodiphenylacetyloylamino group, an iododiphenylacetyloylamino group, a chloroacetoxyacetyloyloxy group, a bromoacetoxyacetyloyloxy group, an iodoacetoxyacetyloylamino group, a chloroacetoxyacetyloyloxy group, a bromoacetoxyacetyloylamino group, an iodoacetoxyacetyloylamino group, etc. From the viewpoints of polymerizability and availability, etc., a 2-chloropropanoyloxy group, a 2-chloropropanoylamino group, a 2-bromo-2-methylpropanoyloxy group, and a 2-bromo-2-methylpropanoylamino group are preferred.

[0051] As the living radical polymerization method, the ATRP method using a conventionally known metal complex is suitable. As the metal complex, a metal complex having an element of Groups 7 to 11 of the periodic table as a central metal can be used. Specifically, metal complexes containing monovalent copper, divalent copper, divalent ruthenium, divalent iron, and divalent nickel can be mentioned. Among them, metal complexes containing monovalent copper and divalent copper, which are inexpensive and easily available, are preferred, and cuprous chloride, cupric chloride, cuprous bromide, cupric bromide, cuprous iodide, and cupric iodide are more preferred.

[0052] When a copper metal complex is used as a polymerization catalyst, a polyamine is used as a ligand for forming the complex. Examples of polyamines used as ligands include 2,2-bipyridine, dinonyl bipyridine, phenanthroline, tridimethylaminoethylamine, pentamethyldiethylenetriamine, tris[2-(dimethylamino)ethyl]amine, tris(2-picolyl)amine, and N,N,N',N'-tetrakis(2-pyridylmethyl)ethylenediamine. The amount of the metal complex (polymerization catalyst) relative to the methacrylate monomer (i) is preferably 0.001 to 0.1% by mass.

[0053] In order to prevent the deactivation of the catalyst during polymerization, a reducing agent may be used. Examples of the reducing agent include tin dilaurate and ascorbic acid. In addition, an azo-based polymerization initiator such as azobisisobutyronitrile may be added to promote the activation of the polymerization.

[0054] The ATRP method may be bulk polymerization or solution polymerization using an organic solvent or the like. Examples of the organic solvent that can be used include hydrocarbon solvents, ester solvents, glycol solvents, ether solvents, amide solvents, alcohol solvents, sulfoxide solvents, urea solvents, and ionic liquids. By using a solvent with high polarity, the polymerization rate can be increased and the film thickness can be increased, which is preferable. Specifically, it is preferable to use an ionic liquid, and it is more preferable to use an ionic liquid such as a quaternary ammonium salt, an imidazolium salt, a pyridinium salt, a quaternary phosphonium salt, or a guanidinium salt.

[0055] It is also preferable to polymerize the methacrylate monomer (i) in the presence of a general-purpose organic compound that does not use heavy metals. As a method for polymerization in the presence of an organic compound, a reversible catalyst-mediated polymerization method (RCMP method) can be mentioned. Specifically, it is preferable to polymerize by immersing a substrate in a polymerization system containing at least one salt selected from the group consisting of quaternary ammonium halide salts, quaternary phosphonium halide salts, and alkali metal halide salts. This allows polymerization using commercially available inexpensive organic materials and inorganic salts. In addition, since there is no need to remove metals, the burden on the environment can be reduced and the process can be simplified.

[0056] Examples of the quaternary ammonium halide salt include benzyltrimethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetraoctylammonium iodide, nonylpyridinium chloride, and choline chloride. Examples of the quaternary phosphonium halide salt include tetraphenylphosphonium chloride, methyltributylphosphonium bromide, and tetrabutylphosphonium iodide. Examples of the alkali metal halide salt include lithium bromide, potassium iodide, and sodium iodide.

[0057] As the salt, it is preferable to use an iodide salt. By using an iodide salt, living radical polymerization proceeds, and a precursor polymer with a narrower molecular weight distribution can be formed. In addition, it is preferable to use a salt that can be dissolved in a polymerization solution, such as a quaternary ammonium iodide salt, a quaternary phosphonium iodide salt, and an alkali metal iodide salt, and it is more preferable to use a quaternary ammonium iodide salt. Examples of the quaternary ammonium iodide salt include benzyltetrabutylammonium iodide, tetrabutylammonium iodide, tetraoctylammonium iodide, dedosyltrimethylammonium iodide, octadecyltrimethylammonium iodide, and trioctadecylmethylammonium iodide.

[0058] From the viewpoint of increasing the activity and forming a more concentrated and high-molecular-weight precursor polymer, the amount of the salt relative to the polymerization initiating group is preferably at least an equimolar amount, more preferably at least 10 times the molar amount, and particularly preferably at least 100 times the molar amount.

[0059] The polymerization conditions when using a quaternary salt or a halide salt are not particularly limited, and may be conventionally known conditions. The polymerization temperature is preferably 60° C. or higher, and an organic solvent is preferably used as the polymerization solvent. The organic solvent may be any of the above-mentioned organic solvents. Among them, it is preferable to use an organic solvent that dissolves salts, and it is more preferable to use an organic solvent with high polarity such as an alcohol, glycol, amide, urea, sulfoxide, or ionic liquid.

[0060] The pressure when polymerizing the methacrylate monomer (i) in the presence of the substrate having a polymerization initiation group bonded to its surface is normal pressure to 1,000 MPa, preferably 10 to 500 MPa. For example, polymerization is performed while applying pressure uniformly through a medium such as water to the entire polymerization vessel containing the methacrylate monomer (i) and the substrate. By performing radical polymerization under pressurized conditions, preferably under pressurized conditions of 50 MPa or more, it is possible to suppress the termination reaction and accelerate the propagation reaction to form a precursor polymer with a higher molecular weight. However, it is difficult to prepare a vessel or device that can withstand a pressure of more than 1,000 MPa, and this is not very practical.

[0061] As the molecular weight of the resulting precursor polymer increases, the thickness of the precursor polymer layer formed increases. By increasing the thickness of the precursor polymer layer and the thickness of the surface modification film formed by reacting the precursor with the reactive compound (ii), the substrate surface can be modified to exhibit unprecedented properties.

[0062] As the polymerization vessel, it is preferable to use a vessel that can be sealed and can withstand high pressure. In addition, since pressure needs to be transmitted to the inside of the vessel, it is preferable to use a vessel having a part that deforms under pressure, such as a soft part or an expandable part made of plastic. Specific examples of the polymerization vessel include polyethylene bottles, PET bottles, retort pouches, and blister containers. In addition, it is preferable to use a polymerization vessel formed of a material that is resistant to deformation at the temperature during polymerization and has heat resistance. Furthermore, it is preferable to use a polymerization vessel formed of a material that is resistant to corrosion by organic solvents for polymerization and has properties such as chemical resistance and solvent resistance. Examples of materials that constitute the polymerization vessel include polyolefin resins, fluorine resins, polyester resins, polyamide resins, and engineering plastics. In addition, it is preferable to prevent gas from entering the polymerization vessel as much as possible during polymerization. For example, it is preferable to carry out polymerization in a state where the polymerization solution is charged to 90% or more of the volume of the polymerization vessel.

[0063] <Surface modified substrate> Next, the surface-modified substrate of the present invention will be described. The surface-modified substrate of the present invention comprises a substrate and the above-mentioned surface-modified film provided on the surface of the substrate. The surface-modified substrate can be manufactured by a method similar to the manufacturing method of the above-mentioned surface-modified film.

[0064] The type of substrate is not particularly limited, and any of natural materials, artificial materials, inorganic materials, and organic materials can be used. The shape of the substrate is not particularly limited, and substrates of various shapes such as lumps, fine particles, powders, sheets, films, pellets, and plates can be used. Among them, it is preferable to use a substrate that can withstand the polymerization solution. Examples of substrates include mechanical parts such as metals, metal oxides, metal nitrides, metal carbides, ceramics, wood, silicon compounds, thermoplastic resins, thermosetting resins, cellulose, and glass, as well as films, fibers, and sheets.

[0065] More specific examples of the substrate include silicon substrates, glass substrates, metal plates such as stainless steel, ceramic plates made of ceramics such as alumina, silicon carbide, and boron nitride, ITO films, plate- or film-like substrates such as plastic plates and plastic films, and fibrous substrates such as glass fibers and carbon fibers. The substrate may also be a filler-like substrate such as pigments, silica, and magnetic powder. The surface-modified substrate of the present invention is suitable for use in various fields such as medical materials, electronic materials, display materials, semiconductor materials, machine parts, sliding members, and battery materials. EXAMPLES

[0066] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0067] <Production of surface-modified substrate> Example 1 Several silicon substrates measuring 1 cm x 1 cm were prepared and ultrasonically cleaned with isopropyl alcohol. The silicon substrates were irradiated with UV ozone after cleaning using a chip cleaner (manufactured by Bioforce Nanosciences) to form hydroxyl groups on the surface of the silicon substrate, activating it. The activated silicon substrates were immersed for 12 hours in a container containing 100 parts of ethanol, 10 parts of 28% aqueous ammonia, and 1 part of 2-bromo-2-methylpropionyloxypropyltrimethoxysilane (BPM). The silicon substrates were removed from the container and dried at 80°C for 10 minutes using a dryer.

[0068] 0.0930 parts of copper(I) bromide, 0.6473 parts of dinonyl bipyridine, 28.43 parts of glycidyl methacrylate (GMA) as a methacrylate monomer (i), 28.43 parts of anisole, and 0.01 part of a 1.95% anisole solution of ethyl bromoisobutyrate (free initiator compound, EBIB) were placed in a glass sample bottle and homogenized to obtain a brown polymerization solution.

[0069] Ten parts of the polymerization solution and the silicon substrate were placed in a glass Schlenk tube equipped with a three-way cock. After argon gas was blown in for 30 minutes, the three-way cock was closed and sealed to form an ampoule. The ampoule was placed in a hot water bath at 60°C and polymerized for 8 hours. After cooling, a part of the polymerization solution in the ampoule was sampled, and the number average molecular weight (Mn) of the polymer (precursor polymer (polyGMA)) in terms of polystyrene was measured by GPC using tetrahydrofuran (THF) as a developing solvent, and the molecular weight distribution (PDI (=Mw / Mn)) was calculated. The Mn of the polymer was 420,000 and the PDI was 1.11. The silicon substrate removed from the ampoule was immersed in THF for 12 hours to obtain a modified substrate on which a precursor polymer layer (1) showing rainbow interference was formed. The thickness of the precursor polymer layer (1) measured using a film thickness meter (trade name "F20-UV", Filmetrics) was 265 nm. The graft density of the precursor polymer calculated from the Mn of the precursor polymer, the film thickness and density (=1.2) of the precursor polymer layer (1) was 0.456 / nm 2The surface IR measurement revealed that the ester bond (1,730 cm -1 ) and glycidyl groups (904cm -1 ) IR absorption spectrum was confirmed.

[0070] One part of dimethylaminopropylamine, which is the reactive compound (ii), and one part of methoxypropylene glycol (MPG) were placed in a sample bottle, and the modified substrate on which the precursor polymer layer (1) was formed was immersed and left at 80°C for 1 hour. The modified substrate was removed and ultrasonically cleaned with THF for 30 minutes, and then thoroughly dried in a blower dryer to obtain a surface-modified substrate (CPB-1) on which a surface-modified film was formed. The surface IR was measured and a peak of 1,466 cm, which is characteristic of dimethylaminoethylpropylamine, was observed. -1 and 3,300 cm, which is characteristic of the hydroxyl group formed by ring-opening of the epoxy group. -1 The thickness of the surface-modified film was 390 nm. Since the thickness of the precursor polymer layer was 265 nm, it can be seen that the film thickness increased by reacting with dimethylaminopropylamine. The graft density of the surface-modified polymer constituting the surface-modified film was the same as the graft density of the precursor polymer, so it was 0.456 fibers / nm 2 It can be estimated that:

[0071] Example 2 Two parts of ethanol and 0.5 parts of benzyl chloride were placed in a glass bottle, and the CPB-1 obtained in Example 1 was immersed in the bottle. The bottle was then covered with a lid and reacted at 80°C for 1 hour, after which the bottle was thoroughly washed with ethanol and thoroughly dried by blowing air onto the bottle with an airbrush, yielding a surface-modified substrate (CPB-2) on which a surface-modified film had been formed. The surface IR was measured to be 1,600 cm -1Absorption was observed near the 451 nm region, confirming that the amino groups had been converted to quaternary salts with benzyl chloride. The thickness of the surface-modified film formed was 451 nm, indicating that the conversion of the amino groups to quaternary salts increased the molecular weight and thus the film thickness. When water was dropped onto the surface-modified film, it was confirmed that the water spread widely over the surface and that the contact angle was 10° or less. From the above, it can be seen that a hydrophilic surface-modified film was formed, consisting of a dense polymer brush into which quaternary ammonium bases have been introduced.

[0072] Example 3 Five parts of water and 0.5 parts of lithium bis(trifluoromethanesulfonyl)imide salt were placed in a glass bottle, and the CPB-2 obtained in Example 2 was immersed in the bottle. After reacting at room temperature for 1 hour, the bottle was washed with water and methanol, and thoroughly dried by blowing air onto the bottle with an airbrush to obtain a surface-modified substrate (CPB-3) on which a surface-modified film was formed. The surface IR was measured, and it was found to be 1,135 cm originating from the imide salt. -1 Near and 1,185 cm -1 Absorption was confirmed near the surface of the modified film. The thickness of the formed surface-modified film was 501 nm, and it was confirmed that the film thickness had increased. When water was dropped onto the surface-modified film, it was repelled by the surface, and it was confirmed that the contact angle was 90° or more. It is believed that the reaction with bis(trifluoromethanesulfonyl)imide lithium salt resulted in the replacement of chloride ions with bis(trifluoromethanesulfonyl)imide ions, as well as an increase in molecular weight, which led to an increase in film thickness. It is also believed that the introduction of bis(trifluoromethanesulfonyl)imide groups through salt exchange made the film hydrophobic. From the above, it can be seen that a hydrophobic surface-modified film was formed, which is composed of a dense polymer brush to which a quaternary ammonium bis(trifluoromethanesulfonyl)imide base has been introduced.

[0073] The surface infrared (IR) absorption spectra of the precursor polymer layer (1) and CPB-1 to 3 are shown in Figure 1. As shown in Figure 1, it is possible to produce a surface-modified film formed of a surface-modified polymer, which is a dense polymer brush into which various desired functional groups have been introduced. In addition, the functional groups can be easily converted, and it is possible to form a surface-modified film with various properties.

[0074] In Examples 1 to 3, hydrophilic and hydrophobic surface-modified films could be formed. This shows that it is possible to form a surface-modified film imparted with properties such as water repellency, oil repellency, antifogging, moisture resistance, stain resistance, and fingerprint adhesion resistance. A base precursor polymer layer is formed by a precursor polymer, which is a dense polymer brush having a glycidyl group, and a reactive compound (ii) having a desired functional group is reacted with the precursor polymer, whereby a surface-modified film imparted with properties can be easily formed without forming a film individually with the corresponding monomer.

[0075] Example 4 A silicon substrate (with a polymerization initiator group bonded to the surface) and a polymerization solution similar to those used in Example 1 were prepared. After placing the silicon substrate in a polyethylene sample bottle, the polymerization solution was filled and the lid was closed. The sample bottle was wrapped with tape to prevent leakage of the polymerization solution, and was placed in an aluminum pouch and laminated to prevent air from entering. The aluminum pouch was placed in a high-pressure device (product name "PV-400 series", manufactured by Shin Corporation) containing water as a pressure medium. The mixture was heated to 60°C and pressurized to 400 MPa for polymerization for 4 hours to obtain a modified substrate on which a precursor polymer layer (2) was formed. The Mn of the generated precursor polymer (polyGMA) was 1,250,000, the PDI was 1.24, and the film thickness of the precursor polymer layer (2) was 790 nm. The graft density of the precursor polymer was 0.399 / nm 2 It was.

[0076] One part of polyethylene glycol propylene glycol monomethyl ether monoamine (polyethylene glycol (EO) / polypropylene glycol (PO) molar ratio = 1 / 9, amine value 91.2 mg KOH / g, molecular weight 615, trade name "Jeffamine M-600", manufactured by Huntsman) which is the reactive compound (ii) and two parts of MPG were placed in a glass bottle. The modified substrate on which the precursor polymer layer (2) was formed was immersed, the glass bottle was capped, and the reaction was carried out at 80 ° C for 1 hour. The modified substrate taken out was washed with THF and then dried to obtain a surface modified substrate (CPB-4) on which a surface modified film was formed. The surface IR was measured and the 2,900 cm -1 near 1,100 cm due to ether bonds -1 and 3,000 cm due to the hydroxyl group formed by ring-opening of the epoxy group. -1 The thickness of the surface-modified film was 990 nm.

[0077] (Examples 5 to 8) Surface-modified substrates (CPB-5 to 8) having a surface-modified film formed thereon were obtained in the same manner as in Example 4 described above, except that the conditions were as shown in Table 1. The properties of the obtained CPB-5 to 8 are shown in Table 1. The meanings of the abbreviations in Table 1 are as follows. M-600: Trade name "Jeffamine M-600", manufactured by Huntsman, EO / PO molar ratio = 1 / 9, amine value 91.2 mg KOH / g, molecular weight 615 M-1000: Trade name "Jeffamine M-1000", manufactured by Huntsman, EO / PO molar ratio = 19 / 3, amine value 56.7 mg KOH / g, molecular weight 990 M-2005: Trade name "Jeffamine M-2005", manufactured by Huntsman, EO / PO molar ratio = 6 / 29, amine value 27.0 mg KOH / g, molecular weight 2,078 M-2070: Trade name "Jeffamine M-2070", manufactured by Huntsman, EO / PO molar ratio = 31 / 10, amine value 26.9 mg KOH / g, molecular weight 2,083 M-3085: Trade name "Jeffamine M-3085", manufactured by Huntsman, EO / PO molar ratio = 30 / 8, amine value 19.8 mg KOH / g, molecular weight 2,828

[0078] TIFF0007618171000003.tif89170

[0079] By introducing a polyalkylene glycol chain, it is possible to impart properties such as hydrophilicity and hydrophobicity to the surface-modified film, and by swelling with various solvents such as water, alcohol, and low polarity solvents, it is possible to make the surface-modified film exhibit properties such as lubricity and low friction. Furthermore, since the surface-modified layer can be made soft by introducing a polyalkylene glycol chain, it is possible to impart properties such as tackiness and adhesion. A precursor polymer layer serving as a base is formed by a precursor polymer, which is a dense polymer brush having a reactive functional group such as a glycidyl group, and a reactive compound (ii) having a desired functional group is reacted with the precursor polymer, so that a surface-modified film having the desired properties can be easily formed without forming a film individually with the corresponding monomer.

[0080] Comparative Example 1 61.5 parts of Jeffamine M-600 and 75.7 parts of anisole were placed in a separable flask equipped with a stirrer, a dropping device, and a cooling tube and stirred. 14.2 parts of GMA were dropped at 25°C over 1 hour, and then reacted at 80°C for 2 hours. IR was measured to confirm the disappearance of epoxy groups and the generation of hydroxyl groups. As a result, a macromonomer to which a polyalkylene glycol chain having a molecular weight of 600 was bonded was obtained. Then, an attempt was made to form a surface-modified film on the surface of a silicon substrate (having a polymerization initiator group bonded to the surface) in the same manner as in the above-mentioned Example 4, except that the obtained macromonomer was used instead of GMA. However, the surface of the substrate after the reaction did not show any interference color, and when the surface IR was measured, only a slight absorption derived from the polymer could be confirmed. The film thickness was uncertain and was 10 nm or less. In addition, even if a reactive compound (ii) other than Jeffamine M-600 (reactive compound (ii) in Table 1) was used in the same manner, a surface-modified film with a high film thickness could not be formed. It was confirmed that the polymerization itself had progressed and that a polymer had been produced.

[0081] It is speculated that the molecular weight of the monomer used is large and the monomer itself is bulky, so that the dense polymer like a dense polymer brush was not formed. Also, it is speculated that the use of a monomer with an amino group led to poor generation of a metal catalyst, resulting in poor living radical polymerization, and thus the surface-initiated living radical polymerization did not proceed.

[0082] Example 9 Three silicon substrates (with polymerization initiator groups bonded to the surface) measuring 2 cm x 5 cm x 1 mm were prepared and mounted on a Teflon (registered trademark) jig designed to prevent them from adhering to each other. A modified substrate on which a precursor polymer layer (7) was formed was obtained in the same manner as in Example 4 above, except that the silicon substrates prepared in this way were used. The Mn of the generated precursor polymer (polyGMA) was 1,300,000, the PDI was 1.19, and the film thickness of the precursor polymer layer (7) was 760 nm. The graft density of the precursor polymer was 0.448 / nm 2 It was.

[0083] Five parts of stearylamine, which is the reactive compound (ii), and 45 parts of MPG were placed in a glass container. The modified substrate on which the precursor polymer layer (7) was formed was immersed and reacted at 80°C for 1 hour. The modified substrate was taken out, washed with THF and toluene, and then dried with an airbrush to obtain a surface-modified substrate (CPB-9) on which a surface-modified film was formed. The surface IR was measured, and the 2,920 cm -1 and 2,850 nm -1 Absorption was confirmed near the surface. The thickness of the surface-modified film was 1,023 nm. When water was dropped onto the surface-modified film, it was repelled by the surface, and it was confirmed that the contact angle was 90° or more.

[0084] (Examples 10 and 11) Into two glass bottles, (1) 10 parts of polydimethylsiloxane diamine (molecular weight 4,400, trade name "KF-8012", Shin-Etsu Chemical Co., Ltd.) and 40 parts of toluene; (2) 10 parts of polydimethylsiloxane diamine (molecular weight 11,400, trade name "KF-8008", Shin-Etsu Chemical Co., Ltd.) and 40 parts of toluene were placed, respectively. The modified substrate on which the precursor polymer layer (7) obtained in Example 9 was formed was immersed in each of them and reacted at 80°C for 4 hours. The removed modified substrate was washed with THF and toluene to obtain surface modified substrates (CPB-10 and 11) on which a surface modified film was formed. The surface IR was measured and found to be 1,021 cm specific to polysiloxane. -1 and 1,083 cm -1 Absorption was confirmed around 100 nm. The thickness of the surface modified film formed was 990 nm for CPB-10 and 840 nm for CPB-11. It is presumed that polydimethylsiloxane (molecular weight 11,400), which has a relatively large molecular weight, does not easily penetrate into the interior of the precursor polymer layer, and therefore the thickness of the surface modified film did not increase significantly.

[0085] Example 12 A silicon carbide substrate (a disk having a diameter of 1 cm and a thickness of 2 mm) was prepared, and its surface was activated in the same manner as in Example 1. The activated substrate was immersed for 12 hours in a container containing 100 parts of ethanol, 10 parts of 28% aqueous ammonia solution, and 1 part of 2-iodo-2-methylpropionyloxyhexyltriethoxysilane (IHE). The substrate was removed from the container and dried by blowing air.

[0086] A glass sample bottle was charged with 0.406 parts of tetrabutylammonium iodide (TBAI), 55.07 parts of 2-hydroxyethyl methacrylate as the methacrylate monomer (i), 55.07 parts of 3-methoxy-N,N-dimethylpropionamide (MDMPA), and 0.1 part of a 1.95% solution of ethyl iodobutyrate in MDMPA, and the mixture was homogenized to obtain a brown, transparent polymerization solution.

[0087] The above-mentioned substrate was placed in a sample bottle made of fluororesin, and the sample bottle was filled with the polymerization solution and sealed, and then placed in an aluminum pouch and laminated to prevent air from entering. The aluminum pouch was placed in a high-pressure device, heated to 85°C, and pressurized to 100 MPa for polymerization for 6 hours to obtain a modified substrate on which a precursor polymer layer (8) was formed. The Mn of the resulting precursor polymer was 240,000, the PDI was 1.42, and the thickness of the precursor polymer layer (8) was 120 nm. The graft density of the precursor polymer was 0.361 fibers / nm 2 It was.

[0088] 50 parts of 3-methoxy-N,N-dimethylpropionamide, 5 parts of trimellitic anhydride, which is the reactive compound (ii), and 0.1 parts of dimethylaminopyridine were placed in a glass container. The modified substrate on which the precursor polymer layer (8) was formed was immersed and reacted at 90°C for 5 hours. The modified substrate was taken out, washed with THF, and then thoroughly dried with an airbrush to obtain a surface-modified substrate (CPB-12) on which a surface-modified film was formed. The surface IR was measured, and the 1,800 cm -1 near 1,730 cm due to the ester bond -1 near 1,700 cm due to the carboxyl group-1 Near 1,230 cm, derived from trimellitic acid -1 , 1,114cm -1 , and 1,060 cm -1 Absorption was confirmed near the surface of the polymer. The thickness of the surface-modified film formed was 180 nm. When attempting to form a concentrated polymer brush having a carboxyl group by conventional atom transfer radical polymerization, the reaction cannot proceed well because the metal catalyst cannot be formed due to the influence of the carboxyl group. In contrast, as described above, a surface-modified film formed of a concentrated polymer brush (surface-modified polymer) having a carboxyl group can be obtained by reacting an acid anhydride with a concentrated polymer brush (precursor polymer) having a hydroxyl group. By appropriately selecting the type of acid anhydride used as the reactive compound (ii), a surface-modified film formed of a surface-modified polymer having various groups can be obtained.

[0089] Example 13 A 0.5% aqueous solution of sodium hydroxide was placed in a beaker, and the CPB-12 obtained in Example 12 was immersed in the beaker. After immersion at 25°C for 1 minute, the beaker was removed, washed with water and methanol, and dried by air spray to obtain a surface-modified substrate (CPB-13) on which a surface-modified film was formed. When the surface IR was measured, the absorption due to the carboxyl group disappeared, and the absorption at 1,570 cm -1 It was confirmed that a broad absorption was formed near the ionic group. This suggests that the carboxyl group was neutralized by the alkali to form a neutralized salt. The thickness of the surface-modified film formed was 193 nm. When water was dropped onto the surface-modified film, it was confirmed that the water spread over the surface and the contact angle was 10° or less. It is suggested that the surface-modified film having ionic groups formed in this way is hydrophilic and also exhibits properties such as electrical conductivity and ion mobility.

[0090] Example 14 100 parts of propylene glycol monomethyl ether acetate (PGMAc) was placed in a reactor equipped with a stirrer, reflux condenser, thermometer, and nitrogen inlet tube, and the mixture was heated to 80°C and nitrogen gas was blown in. 50 parts of 2-(2-bromoisobutyryloxy)ethyl methacrylate (BBEM), 50 parts of methacryloyloxypropyltriethoxysilyl (MOPS), and 1.5 parts of azobisisobutyronitrile (AIBN) were placed in a separate container and stirred to prepare a homogeneous monomer mixture. After adding half of the monomer mixture to the reactor, the remainder was dropped over 2 hours, and then polymerized for 8 hours to obtain a polymer liquid. A part of the polymer liquid was sampled and measured for a solid content of 49.2%, confirming that most of the monomers had polymerized. The Mn of the polymer in the polymer liquid was 23,000, and the PDI was 2.51. The obtained polymer liquid was diluted with PGMAc to obtain an initiator polymer 1 solution with a solid content of 15%. The initiator polymer 1 in the initiator polymer 1 solution is a polymer-type initiator-containing surface treatment agent having a 2-bromoisobutyryloxy group, which is a polymerization initiating group, and an alkoxysilyl group capable of reacting with a substrate.

[0091] A glass substrate of 3 cm x 3 cm was prepared, and the surface was activated in the same manner as in Example 1. The prepared initiator polymer 1 solution was then spin-coated onto the glass substrate at 2,000 rpm for 30 seconds, and then baked at 90°C for 90 seconds and at 150°C for 10 minutes to harden the substrate, forming a coating film. The coating film thus formed had a thickness of 1.00 μm.

[0092] A modified substrate having a precursor polymer layer (9) formed on a glass substrate was obtained in the same manner as in Example 4, except that the glass substrate on which the coating film was formed was used and that methacryloyloxyethyl isocyanate was used instead of GMA. The Mn of the generated precursor polymer was 1,010,000, the PDI was 1.54, and the thickness of the precursor polymer layer (9) (including the thickness of the coating film formed with the initiator polymer 1) was 1.67 μm. The graft density of the precursor polymer calculated assuming a density of 1.2 was 0.479 fibers / nm 2That is, the thickness of the precursor polymer layer (9) formed on the coating film was 670 nm. Surface IR was measured, and the 2,200 cm -1 Absorption was confirmed in the vicinity.

[0093] Using lauryl alcohol as an initiator and tetrabutyl titanate as a catalyst, epsilon caprolactone was subjected to ring-opening polymerization to prepare polyepsilon caprolactone with a hydroxyl value of 27.3 mg KOH / g and a converted molecular weight of 2,050. 10 parts of polyepsilon caprolactone, which is the reactive compound (ii), 40 parts of toluene, and 0.012 parts of tin dilaurate were placed in a glass bottle. The modified substrate on which the precursor polymer layer (9) was formed was immersed and reacted at 90 ° C for 24 hours. The removed modified substrate was washed with toluene and methyl ethyl ketone and then thoroughly dried to obtain a surface modified substrate (CPB-14) on which a surface modified film was formed. Surface IR was measured to determine the disappearance of absorption due to isocyanate groups and the disappearance of absorption at 1,190 cm due to polyepsilon caprolactone. -1 The absorption near the nucleus was confirmed, and the peak due to the ester bond was confirmed to have increased. The thickness of the surface-modified film was 875 nm. [Industrial Applicability]

[0094] The surface modified film of the present invention is useful as a material applied to parts of automobiles, aircraft, electronic devices, home appliances, battery members, medical materials, display materials, and the like.

Claims

1. A film-like substance having a thickness of 100 nm to 10 μm is provided on a surface of a substrate, the film including a precursor polymer stretched from a polymerization initiation group of a substrate having a constitutional unit derived from a methacrylate monomer (i) and having a polymerization initiation group bonded to the surface of the substrate, the precursor polymer being a reaction product of the precursor polymer and a reactive compound (ii); the methacrylate monomer (i) is at least one selected from the group consisting of hydroxyalkyl methacrylate, glycidyl methacrylate, epoxycyclohexylmethyl methacrylate, methacryloyloxyethyl isocyanate, and a methacryloyloxyethyl isocyanate derivative in which an isocyanate group is blocked; the reactive compound (ii) is at least one selected from the group consisting of a compound having an amino group, a hydroxyl group, or a carboxy group, a carboxylic acid anhydride, and an acid halide; The molecular weight of the reactive compound (ii) is 500 to 20,000; The graft density of the surface modifying polymer on the surface of the substrate is 0.1 to 1 / nm 2 A surface modified membrane.

2. The surface modified film according to claim 1 , wherein the polymerization initiating group is a group represented by the following general formula (1): (In the general formula (1), R 1 represents a hydrogen atom, an alkyl group, an acyl group, or an aryl group; R 2 represents an alkyl group or an aryl group, X represents a chlorine atom, a bromine atom, or an iodine atom, and Y represents O or NH.

3. The precursor polymer has a number average molecular weight of 200,000 to 5,000,000; 3. The surface modified film according to claim 1, wherein the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.05 to 2.

0.

4. The surface modified film according to any one of claims 1 to 3, which is a film having a thickness of 400 nm to 10 µm.

5. The surface modified film according to any one of claims 1 to 4, wherein the reactive compound (ii) is at least one of a compound having a polyalkylene glycol chain and a compound having a polydimethylsiloxane chain.

6. A method for producing a surface modified film according to any one of claims 1 to 5, A step (1) of subjecting at least one methacrylate monomer (i) selected from the group consisting of hydroxyalkyl methacrylate, glycidyl methacrylate, epoxycyclohexylmethyl methacrylate, methacryloyloxyethyl isocyanate, and methacryloyloxyethyl isocyanate having a blocked isocyanate group to surface-initiated radical polymerization or surface-initiated living radical polymerization in the presence of a substrate having a polymerization initiator group bonded to its surface under a pressure condition of normal pressure to 1,000 MPa to form a precursor polymer layer containing a precursor polymer extended from the polymerization initiator group; (2) reacting at least one reactive compound (ii) selected from the group consisting of a compound having an amino group, a hydroxyl group, or a carboxy group, a carboxylic acid anhydride, and an acid halide with the precursor polymer to form a surface-modified film containing a surface-modified polymer; A method for producing a surface modified film having the above structure.

7. The method for producing a surface modified film according to claim 6, wherein in the step (1), the methacrylate (i) is subjected to surface-initiated living radical polymerization under a pressure condition of 10 to 500 MPa.

8. A surface-modified substrate comprising a substrate and the surface-modified film according to any one of claims 1 to 5 provided on a surface of the substrate.

Citation Information

Patent Citations

  • Method for covering surface of material

    JP2001158813A

  • Surface-hydrophilic polyolefin molding and method for producing the same

    JP2008133434A

  • Radionuclide capturing material, radionuclide capturing cartridge, manufacturing method, and separation method

    JP2009063354A

  • Surface-decorated base material and polymer-coated base material

    JP2010261001A

  • Polymer coating inorganic fine particle, manufacturing method therefor and material therefor

    JP2015140397A